Joint determination of internal organizational design: Decision-making, task allocation, and incentive scheme - Son Ku Kim; Keunkwan Ryu (Osaka University, Institute of Social and Economic Research (ISER), 2001)
This paper studies the issue of designing an optimal organizational form: design for sub-units' task allocation, decision-making structure, and incentive schemes for organizational members. Depending on the way tasks are allocated between the sub-units, and whether decision-making is centralized or not, organizations face a trade-off between coordination and information. Task allocation by production processes calls for coordination more strongly than the allocation by final products. Centralized decision-making serves for better coordination, whereas decentralization serves for better information. The coordinational benefit under centralization gets bigger as the organization's common uncertainty increases, and this benefit is magnified when the sub-units are functionally divided by production processes. The informational benefit under decentralization gets bigger as the organization's local uncertainty increases, and this benefit is magnified when the sub-units are designed autonomous. Thus, complementarily designed organizations tend to have centralized decision-making structures and fixed salary scheme, whereas less complementarily designed organizations tend to have decentralized decision-making and 'pay for performance' incentive contract.
Keywords: 330; agency problem; complementarity; decision-making structure; incentive contract; task allocation; Organisationstheorie; Prinzipal-Agent-Theorie; Anreizvertrag; Organisationsstruktur; Theorie; Mehrstufige Entscheidung